2005
DOI: 10.1139/v05-179
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of the 1,3-dipolar cycloaddition reaction mechanism for nitrilimines

Abstract: The [3+2] and [1+2] cycloaddition pathways between ethene and a series of 13 nitrilimines (R1CNNR2) have been examined by density functional theory [PBE0/6-311++G(2df,pd)] calculations. All reactions have low barriers ranging from 14.14 (R1 = CH3, R2 = H) to 1.01 (R1 = R2 = F) kcal mol–1, and large reaction exothermicities consistent with the transient nature of nitrilimines. The [3+2] and [1+2] transition-state structures are very similar, mainly differing in the relative orientation of their fragments and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 70 publications
1
21
0
2
Order By: Relevance
“…For example, Quideau and co-workers have shown that a bis-pericyclic Diels-Alder transition state controls diastereofacial selectivity in the dimerization of ortho-quinols for the synthesis of (+)-aquaticol, a bis-sesquiterpene. [60] Cycloaddition bifurcations were also reported for the reaction of 1,2,4,5-tetrazines and pyridazines with alkynes, the cycloaddition of cycloheptatriene and cyclopentadiene, [61] 1,3-dipolar cycloadditions, [62] and dichlorocarbene addition to cyclopropene.…”
Section: Cycloadditionsmentioning
confidence: 82%
“…For example, Quideau and co-workers have shown that a bis-pericyclic Diels-Alder transition state controls diastereofacial selectivity in the dimerization of ortho-quinols for the synthesis of (+)-aquaticol, a bis-sesquiterpene. [60] Cycloaddition bifurcations were also reported for the reaction of 1,2,4,5-tetrazines and pyridazines with alkynes, the cycloaddition of cycloheptatriene and cyclopentadiene, [61] 1,3-dipolar cycloadditions, [62] and dichlorocarbene addition to cyclopropene.…”
Section: Cycloadditionsmentioning
confidence: 82%
“…As Figure details, the electronic structure of isothiirane can be tuned through substitution and by modifying their donor/acceptor abilities may result in carbenic and/or 1,3‐dipole reactivity. This make isothiirane a molecule with potential value in [1+2] or [3+2] cycloadditions, similar to substituted cyclopropanes and nitrilimines, and would provide a new means of incorporating sulfur into a ring system.…”
Section: Resultsmentioning
confidence: 99%
“…berichtet, dass bei der Synthese des Bissesquiterpens (+)‐Aquaticol die diastereofaciale Selektivität der Dimerisierung von ortho ‐Chinolen durch einen bispericyclischen DA‐Übergangszustand gesteuert wird 60. Darüber hinaus sind Bifurkationen bei Cycloadditionen für die Reaktion von 1,2,4,5‐Tetrazinen und Pyridazinen mit Alkinen, Cycloadditionen zwischen Cycloheptatrien und Cyclopentadien,61 1,3‐Dipolare Cycloadditionen62 und die Addition von Dichlorcarben an Cyclopropen beschrieben 63…”
Section: Pericyclische Reaktionenunclassified